Analisis Tebal Perkerasan dan Biaya Dengan Software Faarfield Pada Landas Pacu BIJB Kertajati - Palino, Silvani Desy; Susilo, Budi Hartanto (Jurnal Teknik Sipil, 2021)
An airport that was constructed and used for air traffic certainly repented of the action of thickness analysis and evaluation of thickness that could withstand the burden of traffic movements. Accordingly, the purpose of this research is to analyse runway pavement thickness that used is FAA Method Advisory Curcular no. 150/5320-6E through FAARFIELD software and the result is a total thickness of 814, 9mm with surface course thickness of 200 mm, base course thickness of 127 mm, and subbase course thickness of 487,9 mm. Evaluation thickness the stucture strength which is PCN score through two methods ICAO and FAA based on AC 150/5335-5C by using COMFAA software and by calculating ACN score which is the number that become a certain aircraft limitation toward the pavement.PCN score ICAO method is 89/F/C/X/T < ACN is 89,3 and FAA method is 101,4/F/C/X/T > ACN is 89,3. The result of mininum construction cost analysis from 5 comparative is a method of software FAARFIELD of Rp.326.252.664.418,00.